Epistemologi Ilmu Pengetahuan: Pengertian, Ruang Lingkup, Dan Implikasinya Dalam Konteks Keilmuan Modern - Hidayati, Zulfa Rahmat; Syukri, Ahmad; Yenti, Zarfina (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Epistemology is a branch of philosophy that focuses on the nature, sources, methods, and limits of human knowledge. This article aims to examine the concept of epistemology within the context of the philosophy of science, its scope, and its relevance to the development of modern scientific thought. This study employs a descriptive qualitative approach using a literature review method thatdraws upon both classical and contemporary sources in the field of the philosophy of science. The findings indicate that epistemology encompasses four main domains: the sources of knowledge, the methods of acquiring knowledge, the validity and truth of knowledge, and the limits of human understanding. In the modern context, epistemology faces new challenges such as technological advancement, scientific interdisciplinarity, and the relationship between local and global knowledge systems. The practical implications of epistemology are also evident in education through constructivism, inquiry-based learning, and epistemological literacy. Therefore, a sound understanding of epistemology serves as a crucial foundation for developing an educational and scientific system that is critical, reflective, and contextually relevant.